Vinegar intake in patients undergoing immune checkpoint inhibitor therapy: food frequency questionnaire study - Ariizumi, Hirotsugu; Shimazui, Miyuki; Ogawa, Chisato; Kaneki, Mika; Saito, Nanaho; Mura, Emiko; Suzuki, Risako; Tsurui, Toshiaki; Iriguchi, Nana; Ishiguro, Tomoyuki; Hirasawa, Yuya; Shimokawa, Masahiro; et al. (Frontiers in Immunology, 2025)
IntroductionThe gut microbiome is increasingly recognized as a key modulator of immune checkpoint inhibitor (ICI) efficacy. Dietary factors, particularly fibers, may influence the microbiome and thus affect the ICI response. Although Western studies have suggested a link between high fiber intake and better outcomes, this relationship remains unclear in Japanese populations with different dietary habits. This study investigated dietary components associated with ICI response in Japanese patients with cancer.MethodsIn total, 32 patients with carcinomas treated with ICIs were enrolled. Nutritional customs before ICI infusion were analyzed using a food frequency questionnaire.ResultsAmong the 331 dietary items, only vinegar (acetic acid) intake showed an independent association with the treatment response. Higher vinegar consumption correlated with significantly lower odds of nonresponse (P = 0.017). In contrast, total and fermentable dietary fiber intake showed no significant association with ICI efficacy or survival outcomes.ConclusionsHigher vinegar intake is associated with better ICI response in Japanese patients, whereas fiber has a limited effect. Thus, tailored dietary strategies are needed for optimal outcomes.